A thematic review on traditional handicraft from design perspective publications from 2002–2022: analysis of trends for future studies - Liu, Haoran; Alli, Hassan; Md Yusoff, Irwan Syah (Cogent OA, 2024)
Traditional handicraft sector become a new mechanism for sustainable development, employment opportunities, and economic growth in rural areas of China. To find out current issues and trends of Chinese traditional handicraft product development, a systematic study is required to analyze the state-of-art of topic under investigation. Secondary data through literature review is used to obtain data in Scopus database from 2002 to 2022 by using the Citespace visualization software. Bibliometric analysis focus on annual number of articles, journals, authors’ cooperation, issuing institutions and keywords to explore an information. The results indicated that the Chinese traditional handicraft product has been highlighted as most significant topic discussing by scholars and researchers since few years ago. Specific topic of study divided into three stages: slow start, fluctuating growth and rapid development. The specific topic rise on issue such as sustainability, innovation, employment, and perceptions. Furthermore, the research directions can be acknowledged in theoretical concepts and methodological model. Based on these findings, this study further discusses the potential impact on the management level.